THE ANALYSIS OF STUDENT’S MATHEMATICAL COMMUNICATION IN SOLVING SOLID FIGURES PROBLEMS REVIEWED FROM STUDENT’S LEARNING STYLES IN FIFTH GRADE OF SD NEGERI 4 KUTOSARI IN ACADEMIC YEAR OF 2020/2021 - Hasna Nur Hanifah; Muhamad Chamdani; Tri Saptuti Susiani (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2021)
The research aimed to describe the level of student's mathematical communication skills in solving solid figures problems reviewed from learning styles to fifth grade students of SD Negeri 4 Kutosari in academic year of 2020/2021. The research was a qualitative approach with case study method. The results showed that from 21 students in fifth grade, there were 9 students having a visual learning style, 7 students having auditory learning style, and 5 students having kinesthetic learning style. Students with visual learning styles had the best level of mathematical communication skills. Students with auditory learning style had good level. Students with kinesthetic learning styles had sufficient level. To improve student’s mathematical communication skills, the teachers provide learning activities based on student’s learning styles.